PERBEDAAN SEMANGAT KERJA PEGAWAI PRIA DAN WANITA PADA KANTOR BUPATI KABUPATEN TOJO UNA-UNA BAGIAN UNIUM DAN PERLENGKAPAN - Muh Gulom (Fakultas Ekonomi Universitas Alkhairaat, 2012)
Implementation tasks and work is an obligation for employees in the organization, both within government organizations and non-governmental organizations. Later in the performance of duties and the job must have a common goal that is expecting the results of the work and tasks as well as satisfactory according to what is specified in advance. To get a good result and work in accordance with the objectives of the organization, each organization can certainly have rules and regulations set forth in a policy. This policy was created with the intention that each component of the organization carrying out duties in accordance with what is stipulated. Issues raised in this study is